Energy Management through Bio-gas Based Electricity Generation System during Load Shedding in Rural Areas - Shah Mohazzem Hossain; Md. Mahadi Hasan (Universitas Ahmad Dahlan, 2018)
The scarcity of energy especially electrical energy is an acute problem and hinders the modern economic development of a country. Most of the time only a small percentage of peoples have access to use continuous electricity supply. But in this modern era, all types of arena like economies, households and companies have extensive demand for electricity which is due to industrialization, extensive urbanization, population growth, rising standard of living and modernization of the agricultural sector of a country. Electricity generation from bio-gas plant through cowdungs of a dairy firm can mitigate the electricity demand to some extends in rural areas, where biogas plant will act act as a backup supply especially during load shedding. This research paper proposed an electricity generation system from bio-gas, which can work as a secondary source of the electricity for all electrical appliances of a particular area in a cost effective manner.